MicroRNA in T-Cell Development and T-Cell Mediated Acute Graft-Versus-Host Disease - Koenecke, Christian; Krueger, Andreas (Frontiers in Immunology, 2018)
Acute Graft-versus-Host Disease (GvHD) is still a major cause of treatment related mortality after allogeneic stem cell transplantation. Allo-antigen recognition of donor T cells after transplantation account for the onset and persistence of this disease. MicroRNAs (miRNAs) are molecular regulators involved in numerous processes during T-cell development, homeostasis and activation. Thus, miRNAs also contribute to pathological T-cell function during GvHD. Given their capacity of fine-tuning T-cell function miRNAs have emerged as promising therapeutic targets to curtail acute GvHD, but simultaneously maintain T-cell mediated Graft-versus-Tumor (GvT) effects. Here we review the role of key miRNAs contributing to the pathophysiology of GvHD. We focus on those miRNAs acting in T cells and for which a role in GvHD has been established in pre-clinical models. Finally, we provide an outlook for clinical application of this new therapeutic target for GvHD prevention and treatment.